Cyber Jurisprudence and the Construction of Digital Legal Awareness Among Generation Z: An Analysis of the Integration of the Taʾdib Concept and MUI Fatwa No. 24 of 2017 - Yogi Saepul Anwar; Abdul Aziz (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study examines the integration of Syed Muhammad Naquib al-Attas’s taʾdib concept with MUI Fatwa No. 24 of 2017 as a philosophical framework for constructing the digital legal awareness of Indonesian Muslim Generation Z. The central problem addressed is the persistently low level of digital legal awareness among Generation Z despite rapid internet and social media penetration, while academic scholarship that simultaneously synthesizes cyber jurisprudence, Islamic educational philosophy, sociological legal consciousness theory, and the behavioral characteristics of Generation Z within a unified analytical framework remains scarce. This study employs a qualitative-descriptive-analytical library research design, utilizing content analysis of primary documents and relevant academic literature as its principal methodological strategy. The findings demonstrate that the taʾdib concept, with its emphasis on the comprehensive formation of adab, is highly pertinent as a philosophical foundation for internalizing cyber jurisprudence norms. MUI Fatwa No. 24/2017, which employs the principles of maqashid al-shariʾah, sadd al-dhariʾah, and al-maslahah, provides concrete Islamic digital legal norms; however, its implementation among Generation Z remains constrained by a significant gap between normative knowledge and actual behavioral compliance. This study proposes the Taʾdib-Cyber Jurisprudence Integration Model (Islamic Cyber Ethics Model, ICEM) as an alternative paradigm for Islamic digital ethics education targeting Generation Z. The principal contribution lies in a novel theoretical framework that integrates classical Islamic educational epistemology with contemporary Islamic legal instruments in the construction of digital legal awareness.